Banking, risk and crises in Europe from the global financial crisis to COVID-19 - Karkowska, Renata; Korzeb, Zbigniew; Matysek-Jędrych, Anna; Niedziółka, Pawel (Routledge international studies in money and banking, 2023)
"European economies have been plagued by successive crises, from the Global Financial Crisis (GFC) to the COVID-19 pandemic, through to the economic and geopolitical instability in Ukraine. These events, the uncertainty they generate combined with dynamic technological progress and significant socio-cultural changes, have profoundly modified the character of modern finance. Understanding what happened, what mechanisms worked, and the reaction of the banking sector, bank customers, and policymakers require an in-depth and structured analysis. This book critically assesses the impact of these events, notably the Covid-19 pandemic, on the performance of the banking sector in Europe and serves as a compendium of knowledge on recent changes in European banking from two perspectives. Firstly, European banking transformation, analyzing the process of what has already taken place: in particular, the GFC and Covid-19 crises; secondly, from the perspective of the challenges facing the operations and strategic management of European banks. It identifies specific areas of impact on the activity of commercial banks and the determining factors that will shape the economic and financial condition of banks and their customers - borrowers - in the future. Risk management, particularly credit risk, is a key focus of this volume. Each chapter, implicitly or explicitly, address a variety of questions that can help the reader to understand the complex nature of the transformation of the banking sector. The book provides a structured reference for those concerned with the impact of volatility on the business models of modern banks. As such, it will find a broad audience among students, academics, banking, financial, business, and industry professionals, policymakers, and market regulators."